2022
DOI: 10.3389/fphar.2022.891802
|View full text |Cite
|
Sign up to set email alerts
|

Yu-Ping-Feng Formula Ameliorates Alveolar-Capillary Barrier Injury Induced by Exhausted-Exercise via Regulation of Cytoskeleton

Abstract: Background: Yu-ping-feng powder (YPF) is a compound traditional Chinese medicine extensively used in China for respiratory diseases. However, the role of YPF in alveolar-capillary barrier dysfunction remains unknown. This study aimed to explore the effect and potential mechanism of YPF on alveolar-capillary barrier injury induced by exhausted exercise.Methods: Male Sprague–Dawley rats were used to establish an exhausted-exercise model by using a motorized rodent treadmill. YPF at doses of 2.18 g/kg was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Within immunocompromised and high-risk older populations, there was a trend towards an increase in the CD4 + /CD8 + ratio, implying that CHM might play a role in enhancing patients’ cellular immunity. Moreover, our analysis unveiled that the preventative effect of CHM against COVID-19 was more pronounced in children and older adults ( Fang et al, 2020 ; Wang et al, 2022 ). We believe that the following factors contribute to this observation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Within immunocompromised and high-risk older populations, there was a trend towards an increase in the CD4 + /CD8 + ratio, implying that CHM might play a role in enhancing patients’ cellular immunity. Moreover, our analysis unveiled that the preventative effect of CHM against COVID-19 was more pronounced in children and older adults ( Fang et al, 2020 ; Wang et al, 2022 ). We believe that the following factors contribute to this observation.…”
Section: Discussionmentioning
confidence: 82%
“…Seven studies had scores lower than four on the modified Jadad scale, indicating poor overall quality of research. The average NOS score for observational studies was 7.4 ( Fang et al, 2020 ; Lv et al, 2020 ; Wang et al, 2020 ; Zheng and Lu, 2021 ; Wang et al, 2022 ), suggesting the high quality of the included studies. The summary of the included studies in the analysis were shown in Table 4 and Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial barrier integrity is closely associated with the pulmonary function as well as the severity of ALI [ 33 , 34 ]. We next observed whether HDAC3 knockout in AT2 affect alveolar epithelial barrier integrity in mice with ALI.…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al ( 18 ) found that through conventional treatment, YPFG significantly relieved clinical symptoms, prevented acute exacerbations, and improved symptom scores in COPD patients with good safety, which may be related to the anti-fatigue and anti-hypoxia functions of astragalus ( 49 ). Animal experiments show that Yupingfeng (YPF) can improve alveolar-capillary barrier damage induced by exhaustive exercise in rats by modulating the cytoskeleton ( 50 ).…”
Section: Discussionmentioning
confidence: 99%